Safety, privacy, or both: evaluating citizens’ perspectives around artificial intelligence use by police forces - Ezzeddine, Yasmine (Policing and society, 2023)
Police forces are increasing their use of artificial intelligence (AI) capabilities for security purposes. However, citizens are often aware and cautious about advanced policing capabilities which can impact negatively on the perceived legitimacy of policing efforts and police more generally. This study explores citizens’ subjective perspectives to police use by AI, including tensions between security, privacy, and resistance. Using Q methodology with 43 participants in the UK, Netherlands, and Germany we identified five distinct perspectives towards AI use by police forces. The five perspectives illustrate the complex, diverse viewpoints citizens exhibit with respect to AI use by police and highlight that citizens’ perspectives are more complex than often portrayed. Our findings offer theoretical and practical implications for public engagement around general versus personal safety, privacy and potentials for moral dilemmas and counter-reactions.